2009 10th International Conference on Ultimate Integration of Silicon 2009
DOI: 10.1109/ulis.2009.4897607
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Rich Oxide with controlled mean size of silicon nanocrystals by deposition in multilayers

Abstract: --The size of Si nanocrystals in Silicon Rich Oxide has been varied by depositing this material in multilayer arrays. They are possible candidates for one dimensional quantum devices. A study based on TEM, Raman and XRD measurements is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…By larger R 0 's, Si is in amorphous state or dispersed in the oxide matrix. Figure 7 shows a plot of the sizes of the Si-ncs versus R 0 [17,22,23]. As can be observed, the Si-nc size decreases almost linearly with the increasing of R 0 , for R 0 's above 3.…”
Section: Composition Of Sro By Lpcvdmentioning
confidence: 76%
“…By larger R 0 's, Si is in amorphous state or dispersed in the oxide matrix. Figure 7 shows a plot of the sizes of the Si-ncs versus R 0 [17,22,23]. As can be observed, the Si-nc size decreases almost linearly with the increasing of R 0 , for R 0 's above 3.…”
Section: Composition Of Sro By Lpcvdmentioning
confidence: 76%
“…The most prominent Raman peak of Si, located at about 521 cm -1 (TO mode at the center of the Brillouin zone) was tracked to analyze its asymmetry. It has been reported that the presence of nanocrystalline Si, or nanometric Si features may induce an asymmetry of this peak, and this asymmetry can be used to estimate nanocrystallite sizes (14). A measure of asymmetry is the ratio LWHM/RWHM (Left Width at Half Maximum / Right Width at Half Maximum); however, as the asymmetry is not pronounced in the present samples, the widths were taken at a quarter of the maximum (the ratio is then LWQM / RWQM) to have larger values and reduce errors.…”
Section: Raman Microscopymentioning
confidence: 99%